Characterization of the Therapeutic Profile of Albiflorin for the Metabolic Syndrome - Zhou, Xiu; Fouda, Sherouk; Zeng, Xiao-Yi; Li, Dongli; Zhang, Kun; Xu, Jun; Ye, Ji-Ming (Frontiers in Pharmacology, 2019)
Albiflorin (AF) is a small molecule (MW 481) isolated from Paeoniae radix, a plant used as a remedy for various conditions with pathogenesis shared by metabolic diseases. Reported here is our characterization of its therapeutic profiles in three mouse models with distinctive pathological features of metabolic syndrome (MetS). Our results firstly showed that AF alleviated high fat (HF) induced obesity and associated glucose intolerance, suggesting its therapeutic efficacy for MetS. In the type 2 diabetes (T2D) model induced by a combination of HF and low doses of streptozotocin, AF lowered hyperglycaemia and improved insulin-stimulated glucose disposal. In the non-alcoholic steatohepatitis-like model resulting from a HF and high cholesterol (HF-HC) diet, AF reversed the increased liver triglyceride and cholesterol, plasma aspartate aminotransferase, and liver TNFα mRNA levels. Consistent with its effect in promoting glucose disposal in HF-fed mice, AF stimulated glucose uptake and GLUT4 translocation to the plasma membrane in L6 myotubes. However, these effects were unlikely to be associated with activation of insulin, AMPK, ER or cellular stress signalling cascades. Further studies revealed that AF increased the whole-body energy expenditure and physical activity. Taken together, our findings indicate that AF exerts a therapeutic potential for MetS and related diseases possibly by promoting physical activity associated whole-body energy expenditure and glucose uptake in muscle. These effects are possibly mediated by a new mechanism distinct from other therapeutics derived from Chinese medicine.